Crystal structure of methyl 1-(4-fluorobenzyl)-3-phenyl-1H-pyrazole-5-carboxylate, C18H15FN2O2 - Xu Wen-Chang (Zeitschrift für Kristallographie - New Crystal Structures, 2017)
C18H15FN2O2, triclinic, P1̅ (no. 2), a = 7.8272(8) Å, b = 9.6662(10) Å, c = 10.9834(12) Å, α = 107.859(2)°, β = 92.559(2)°, γ = 99.415(2)°, V = 776.31(14) Å3, Z = 2, Rgt(F) = 0.0407, wRref(F2) = 0.1187, T = 296 K.